Novel Partial Exon 51 Deletion in the Duchenne Muscular Dystrophy Gene Identified via Whole Exome Sequencing and Long-Read Whole-Genome Sequencing - Li, Qianqian; Chen, Zhanni; Xiong, Hui; Li, Ranran; Yu, Chenguang; Meng, Jingjing; Shi, Panlai; Kong, Xiangdong (Frontiers in Genetics, 2021)
Duchenne muscular dystrophy (DMD), one of the most common progressive and severely disabling neuromuscular diseases in children, can be largely attributed to the loss of function of the DMD gene on chromosome Xp21.2-p21.1. This paper describes the case of a 10-year-old boy diagnosed with DMD. Whole exome sequencing confirmed the hypothesized large partial exonic deletion of c.7310-11543_7359del (chrX:g.31792260_31803852del) spanning exon 51 and intron 50 in DMD. This large deletion was verified to be de novo by polymerase chain reaction, and the two breakpoints were further confirmed by Sanger sequencing and long-read whole-genome sequencing. Notably, this partial exonic deletion was the only complex variation in the deep intron regions or intron-exon junction regions in DMD. Additionally, the case study demonstrates the clinical importance of using multiple molecular genetic testing methods for the diagnosis of rare diseases.